Предмет: Алгебра,
автор: Kluny
(6^x)+6*(25^x)-6=(5^x)*(30^x)
(Решить разложением на множители)
Ответы
Автор ответа:
0
(6^x)+6*(25^x)-6=(5^x)*(30^x)=150^x=(6^x)*(25^x)
6(6^(x-1)-1)=(6^x)*(25^x)-6*(25^x)=6*25^x(6^(x-1)-1)
6(6^(x-1)-1)=6*25^x(6^(x-1)-1) сократить на 6 только!!!
(6^(x-1)-1) - 25^x(6^(x-1)-1)=0
(6^(x-1)-1)*(1-25^x)=0
6^(x-1)-1=0 --->x-1=0---->x=1
1-25^x=0 --->x=0
6(6^(x-1)-1)=(6^x)*(25^x)-6*(25^x)=6*25^x(6^(x-1)-1)
6(6^(x-1)-1)=6*25^x(6^(x-1)-1) сократить на 6 только!!!
(6^(x-1)-1) - 25^x(6^(x-1)-1)=0
(6^(x-1)-1)*(1-25^x)=0
6^(x-1)-1=0 --->x-1=0---->x=1
1-25^x=0 --->x=0
Похожие вопросы
Предмет: Математика,
автор: alexneon
Предмет: Математика,
автор: Аноним
Предмет: История,
автор: moldirtoken05
Предмет: Физика,
автор: DenarF
Предмет: Математика,
автор: Диана299